2015
DOI: 10.1152/japplphysiol.00154.2015
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of blood glucose levels in the rat following exposure to hyperbaric oxygen

Abstract: Findings regarding blood glucose level (BGL) on exposure to hyperbaric oxygen (HBO) are contradictory. We investigated the influence of HBO on BGL, and of BGL on latency to central nervous system oxygen toxicity (CNS-OT). The study was conducted on five groups of rats: Group 1, exposure to oxygen at 2.5 atmospheres absolute (ATA), 90 min/day for 7 days; Group 2, exposure to oxygen once a week from 2 to 6 ATA in increments of 1 ATA/wk, for a period of time calculated as 60% of the latency to CNS-OT (no convulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…At day 21, ketosis was confirmed by measuring β‐hydroxybutyrate and glucose levels in two drops of blood taken from the tail vein of KD fed rats using FreeStyle optium neo blood ketone and glucose monitoring system obtained from Abbott Diabetes Care Inc. (USA). In our study, all rats in KD and KD + SE groups showed hypoglycemia (42.6 ± 4.01 & 44.3 ± 3.9 mg/dl, respectively) and ketosis (blood β‐hydroxybutyrate = 4.61 ± 0.39 & 5.61 ± 0.47 mmol/L, respectively) which were in line with Eynan et al (2015) and Linard et al (2010) respectively. KD was noted to cause a significant weight loss when consumed by normal or epileptic rats.…”
Section: Methodssupporting
confidence: 91%
“…At day 21, ketosis was confirmed by measuring β‐hydroxybutyrate and glucose levels in two drops of blood taken from the tail vein of KD fed rats using FreeStyle optium neo blood ketone and glucose monitoring system obtained from Abbott Diabetes Care Inc. (USA). In our study, all rats in KD and KD + SE groups showed hypoglycemia (42.6 ± 4.01 & 44.3 ± 3.9 mg/dl, respectively) and ketosis (blood β‐hydroxybutyrate = 4.61 ± 0.39 & 5.61 ± 0.47 mmol/L, respectively) which were in line with Eynan et al (2015) and Linard et al (2010) respectively. KD was noted to cause a significant weight loss when consumed by normal or epileptic rats.…”
Section: Methodssupporting
confidence: 91%
“…Another study reported unaltered blood glucose levels when exposing healthy rats to HBO up to 4 ATA (Eynan et al. ). In that study, pressure above 4 ATA was reported to increase blood glucose levels; therefore, it was suggested that HBO therapy induces glycogen depletion and insulin resistance mediated by the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…; Eynan et al. ) used a very short time interval between HBO therapy and the subsequent examination of its effects. The difference between the acute and delayed examinations suggests a potentially delayed conditioning effect of the HBO therapy, which might differentiate the acute and long‐term HBO effects.…”
Section: Discussionmentioning
confidence: 99%
“…This notation comprises the fraction of O 2 in inspired air in the case of in vivo studies, the O 2 content in the atmosphere where cells are cultured in the case of in vitro studies, etc. F I O 2 values <0.21 and >0.21 refer to hypoxia and hyperoxia, respectively] under hyperbaric conditions (2.5 atm) reduces the blood glucose level in rats [ 15 ], only a few studies have examined the effects of hyperoxia on bioenergetics metabolism. The prevalent context of such studies is a post-stroke situation where hyperoxia is used as part the therapeutic interventions aimed at salvaging neurons at risk.…”
Section: Metabolic Responsementioning
confidence: 99%